Korelasi antara Sikap dan Motivasi Belajar Peserta Didik terhadap Hasil Belajar pada Pembelajaran Geografi Kelas X di SMA Negeri 1 Palupuh - Sari, Widya Indah Permata; Anwar, Syafri (Lembaga Yasin AlSys, 2024)
Students who have a good learning attitude and are supported by high learning motivation have a positive influence on learning outcomes. The better the learning attitude and the higher the learning motivation, the higher the learning outcomes. Attitude and motivation to learn are factors that influence learning outcomes. The method used in this research is quantitative with a correlational research type. The sample in this study was 91 students in class learning outcomes reached up to 64.6%, 3) there was a significant correlation between students' learning attitudes and motivation and learning outcomes reaching up to 70.6%. The conclusion of this research is that there is a significant relationship between attitudes and learning motivation together with the learning outcomes of class X students at SMA N 01 Palupuh.